(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
In this article, the main theme of the series, characteristic images, subjective organization of the text, means of connecting the texts, composition, integrity of the theme, and chronotope are considered as specific elements of the formation of poetic series. Attention is paid to showing the main properties of the series such as thematic affinity, motive or idea, lyrical hero, unity of chronotope, compositional harmony, the title of the series, the structure and rhythm of the poems, and the most important, imagery. The fact that it is appropriate to study the issues of artistic conditionality in the genre in relation to its properties, the increase in the weight of artistic conditionality in realistic works - the widespread use of symbolic and figurative images within the framework of realism - is the basis for the emergence of works written in a non-realistic way. conclusions were reached